Clinical Outcomes for PD-1 Inhibitor Plus Chemotherapy as Second-Line or Later Therapy Compared to PD-1/PD-L1 Inhibitor Alone in Advanced Non-small-cell Lung Cancer - Zhai, Xiaoyang; Jing, Xuquan; Li, Ji; Tian, Yaru; Xu, Shuhui; Wang, Min; Zhu, Hui (Frontiers in Oncology, 2020)
Background: Programmed death-1(PD-1)/programmed death-ligand 1(PD-L1) inhibitor monotherapy has been approved as second-line or later therapy in advanced non-small-cell lung cancer (NSCLC). The study aimed to compare the clinical outcomes of PD-1 inhibitor plus chemotherapy with PD-1/PD-L1 inhibitor monotherapy as second-line or later therapy in advanced NSCLC. Methods: The clinical data of patients with advanced NSCLC who received PD-1/PD-L1 inhibitors as second-line or later line therapy was retrospectively collected. Patients were assigned to one of the two groups according to the therapeutic modality used: PD-1/PD-L1 inhibitor monotherapy group or PD-1 inhibitor plus chemotherapy combination therapy group. Disease control rate (DCR), progression-free survival (PFS) and overall survival (OS) were evaluated between the two groups. The prognostic effect of the derived neutrophil-to-lymphocyte ratio (dNLR) and lactate dehydrogenase (LDH) on the outcomes was also evaluated. Results: From April 2017 to October 2019, a total of 84 patients were enrolled in the current study. Twenty-six patients (PD-1 inhibitor, n=25; PD-L1 inhibitor, n=1) received PD-1/PD-L1 inhibitor monotherapy, and fifty-eight patients received PD-1 inhibitor plus chemotherapy. The chemotherapy regimens used were as follows: liposome paclitaxel (n=15); nab-paclitaxel (n=12); docetaxel (n=9); pemetrexed (n=6); and others (n=16). The DCR and OS were not significantly different between the two groups. The PFS of the monotherapy group was longer than that of the combination therapy group (mPFS: 9.6 months vs. 4.6 months, P=0.01). Univariate and multivariate analyses suggested that LDH and sex were independent prognostic factors of PFS. In the second-line therapy subgroup of 38 patients, OS and PFS were not significantly different between the two groups. In the subgroup of 46 patients treated beyond the 2nd line, the monotherapy group had a longer PFS (mPFS: 9.6 months vs. 4.2 months, P=0.01). The incidence of any-grade adverse events was not significantly different between the monotherapy group and the combination therapy group (19.2% vs. 18.9%, P=1.000). One patient in the PD-1 inhibitor plus chemotherapy group died of immune-related pneumonitis. Conclusion: The clinical outcomes of PD-1 inhibitor plus chemotherapy as second-line or later therapy were similar to those of PD-1/PD-L1 inhibitor alone in advanced NSCLC.